Implementasi Augmented Reality untuk Pelatihan Operator Mesin Boiler TWA-WTV 300/10 - Trismianto, Devout Prakoso; Paryanto, Paryanto; Munadi, Munadi (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2024)
The aim of this research is to develop an augmented reality application system as a training or support for boiler engine operators in carrying out their activities. The augmented reality application system uses the head-mounted device Microsoft Hololens and environmental detection using markerless of the Vuforia target area, as well as the application integrated with the Blynk IoT platform. Based on the results of testing applications using the blackbox method, augmented reality applications can run according to the created scenarios. The results of the system usability scale (SUS) test conducted on 5 respondents, the expert staff obtained a score of 70.5, and 35 respondents of new users obtained a score of 70.8. The results of both groups of respondents can be categorized as grade C. Respondents also argued that the augmented reality application system developed for the operation of the boiler machine is categorized as OK and acceptable.